Kuwait : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Kuwait. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The strong economic and financial position of Kuwait has improved further, but inflation has risen. The nation has made significant progress on the issues raised in the 2007 consultation. Kuwait's integration into the global economy has been increasing in recent years. Global integration is underpinned by active membership in global and regional trade initiatives and an ongoing push to liberalize domestic regulations. Both the external current account and fiscal positions are projected to remain in large surplus, albeit at declining levels owing to the high import intensity of the planned investment projects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet